Evaluation of Primary Health Care services: study of trends in brazilian thesis (Research, Society and Development, 2020)
This study sought to delineate and analyze trends in Brazilian research, regarding the evaluation of Primary Health Care services, based on the summaries of the theses made in the Brazilian Postgraduate Programs, since 2014 until 2018. It is a narrative review with a search made in the Catalogs of Thesis and Dissertation of the Higher Level Personal Improvement Coordination, in the month of June 2018, combining the key words: evaluation in health; evaluation in health services; Primary Health Care and Basic Care. These words were selected based on the Descriptors in Health Sciences. The documentary corpus included 25 abstracts of theses, which showed the main trends in the production of studies in the area of ​​evaluation, be they major productions from the Southeast region of Brazil, and they mostly used the approach quantitative in the development of their research, evidencing a gap in what refers to the methods used. The consecrated authors with regard to the evaluation of health services were identified in a large part of the theses. The results were distributed in absolute (n) and relative (%) frequencies, and analyzed by the convergence of their results. Finally, the evaluation in the APS contributes to the construction of scientific knowledge, since it is capable of making available important information that benefits the decision making of managers, professionals and advisory bodies. It is suggested, therefore, that new research on trends be made in the framework of the evaluation in PHC.